PENGARUH LINGKUNGAN KERJA DAN KARAKTERISTIK INDIVIDU TERHADAP KINERJA PEGAWAI SEKRETARIAT DPRD KABUPATEN MOROWALI - DEWITRI, EKA (Fakultas Ekonomi Universitas Tadulako, 2018)
The objective of this research is to find out the effect of work environment and individual characteristic on the performance of parliament secretariat employees of Morowali regency.Data were collection through questioners. Testing of research instruments showed valid and reliable results. The sample amounted to 100 respondents and was carried out with saturation or census method. Classic assumption tests used normality test, heteroscedasticity test and multicolinerity test. Data were analyzed thtough multiple linear regression method.The results of the research show that Work Environment and Individual Characteristics simultaneously have positive and significant effect on the Performance of parliament Secretariat employees of Morowali Regency. This is proved by the F test which shows a significant value smaller than 0.05 is 0,000. Work Environment Variables has positive and significant effect on the Performance of parliament Secretariat employees of Morowali Regency, and Individual Characteristics have positive and significant effect on the performance of parliament Secretariat employees of Morowali Regency.